HUBUNGAN SUBJECTIVE WELL-BEINGDENGAN STRES AKADEMIK PADA MAHASISWA MAGISTER - Levina Wicaksono (Perpustakaan Universitas Surabaya, 2018)
This research aims to know the relationshipbetween subjective well-beingwith academic stress.The dimensions of subjective well-being are positive affect, negative affect, and life satisfaction.Participants of this research were43 postgraduate studentsusing purposive sampling and snowball sampling methods. The scales used were Educational Stress Scale for Adolescents (ESSA), Scale of Positive and Negative Experience (SPANE), andSatisfaction With Life Scale (SWLS).Data was analysed using SPSS 22 and Pearson correlations. Results showthere are negative correlations between life satisfaction with academic stress(r = -0,427, p = 0,004)and betweenpositive affect with academicstress(r = -0,406, p = 0,007).These results means higher levels of life satisfaction and positive affect correlated with lower levelsof academic stress.This research also find negative affect and academic stress are positively correlated (r = 0,498, p = 0,001), which meanshigher levels of negative affect correlated with higher levels of academic stress. It is advised to build a good social relationship to help students coping with stress.